Strengthening Collaborative Governance: Implementing the Pentahelix Approach to Address Challenges in the Toba Caldera UNESCO Global Geopark, Indonesia - Betty B.S. Naibaho; Shew Jiuan Su (Geoconservation Research, 2025)
The Toba Caldera UNESCO Global Geopark (TCUGGp), renowned for its exceptional geological and cultural significance, holds great potential to catalyze regional development and community empowerment. However, the TCUGGp received a warning status (yellow card) for revalidation of its status from the UNESCO Global Geoparks Council (UGGpC) in 2024. Here, we explore the shortcomings and challenges in developing, managing, and promoting the geopark using primary and secondary data. We find that the TCUGGp faced significant challenges, including insufficiencies in human resources, financial constraints, low levels of community engagement, infrastructure gaps, and governance issues, which contributed to the warning status. We propose adopting a collaborative governance model based on the Pentahelix approach, integrating academia, business, community, government, and media (ABCGM) to address these challenges. We suggest how to involve the five stakeholders, and practical implementation for future actions for each stakeholder. By these means, we expect the TCUGGp to reverse its warning status and retain its UGGp status while building a better managerial team and sustainable geopark.